Causality Relationship between Happy Family and Family Education with Children's Morals - Rahmah, Aulia (Perhimpunan Sarjana Ekonomi dan Bisnis, 2023)
Having good, devoted and smart children is the hope of all parents. Because there is no happiest thing for both parents except to see a child who has morals. Therefore, parents must be aware of their obligation to shape children's behavior, in fact a child's morals do not come by themselves, but because of the hard efforts of parents to educate their children with all the love, material and morals. This study aims to look at the causal relationship between the formation of children's morals with happiness in the household and family education. Technically this research uses a quantitative approach with multiple linear regression analysis. The subjects of this study were 100 parents in the village of Talang Semut. The research sample was taken by simple random method and the research data was obtained by distributing questionnaires. The results of the study show that there is a linear relationship between children's morals and family conditions. Children who have happy families and their parents care about their education tend to have better morals. This happens because children get a lot of love, understanding, and motivation to achieve a better future.